Degradable PHA / PU composite water-based barrier coating and coated paper product
By utilizing the dual-phase synergistic structure of PHA/PU composite waterborne barrier coatings, the technical challenges of high gas barrier properties, low-temperature heat sealing, and flexibility under thin coatings have been solved, resulting in green packaging materials throughout their entire life cycle and meeting the requirements for bio-based carbon content.
Patent Information
- Application Number
- CN202511383375.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-26
- Publication Date
- 2025-10-31
- Estimated Expiration
- 2045-09-26
AI Technical Summary
Existing technologies struggle to simultaneously achieve high gas barrier properties, low-temperature heat sealing, and flexibility in thin coatings, and traditional coatings often lack sufficient bio-based carbon content to meet the demands of green packaging throughout its entire lifecycle.
A PHA/PU composite waterborne barrier coating is used. Through a specific stabilization system and preparation process, the synergistic effect of PHA and PU is combined to form a two-phase synergistic structure. PHA serves as the main barrier phase, while PU serves as the toughening and heat-sealing phase, ensuring that the overall bio-based carbon content is not less than 94%.
Achieving high barrier properties, excellent low-temperature heat sealability, and outstanding flexibility with extremely low dry coating weight, while providing green packaging solutions throughout the entire life cycle, meeting flexible packaging requirements and passing rigorous sustainability testing.
Smart Images

Figure CN120867134A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biodegradable polymer coatings and provides biodegradable PHA / PU composite water-based barrier coatings and coated paper products. Background Technology
[0002] Currently, paper-based food packaging widely relies on polyethylene (PE) lamination or fluorinated chemical (PFAS) coatings to achieve oil resistance, barrier properties, and heat-sealing performance. However, PE lamination is difficult to re-pulp and is hard to degrade, while PFAS is subject to controversies regarding its durability and health, and is restricted in many places. Water-based barrier coatings have emerged as an alternative due to their low volatile organic compound (VOC) content and industrially applicable coating capabilities.
[0003] In the field of bio-based barrier materials, polyhydroxyalkanoates (PHAs) have attracted attention due to their excellent gas barrier properties and compostability. Existing technologies such as WO2020036843A1 and CA2239980C propose waterborne PHA dispersion coatings, disclosing the dispersion solids content and particle size window, and achieving biodegradable barrier properties on paper or paperboard substrates. CN115698427A uses poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) in conjunction with an adhesive to improve coating defects. Meanwhile, published literature and patents also focus on improving dispersion stability and water resistance, such as US20220033158A1, WO2023049120A1, and EP4239028A1. However, these existing technologies face a core technical challenge: most solutions are based on a single PHA phase or focus on the stability of the dispersion, failing to effectively address the issue of thin coating amounts, i.e., no more than 10 g / m³. 2 Under harsh conditions, how to simultaneously achieve the inherent contradiction of high gas barrier properties, reliable low-temperature heat sealing, and excellent resizing performance is a challenge. In particular, pure PHA coatings, due to their high crystallinity and brittleness, have extremely narrow heat-sealing windows and their barrier properties drop sharply after bending, failing to meet the actual needs of flexible packaging.
[0004] On the other hand, while waterborne polyurethane (PU) possesses excellent flexibility and heat-sealing properties, its gas barrier properties, particularly its ability to block water vapor, are generally poor, making it difficult to use independently as a high-barrier material. Furthermore, many so-called "bio-based" solutions focus solely on the main resin, neglecting the sources of key auxiliary components such as crosslinking agents and plasticizers in the formulation. This results in the coating's overall non-volatile solids bio-based carbon content failing to achieve a truly meaningfully high proportion, which is inconsistent with the concept of full sustainability.
[0005] Therefore, there is an urgent need in this field for a novel technical solution that can simultaneously solve the "three difficulties" of gas barrier, heat sealing, and flexibility in a unified aqueous system through synergistic effects and with extremely low coating amounts. Furthermore, it must ensure that the entire solid system, from the main material to the additives, is derived from renewable resources, thereby providing a truly green closed-loop solution throughout the entire life cycle. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a biodegradable PHA / PU composite water-based barrier coating and coated paper products. By introducing a specific stabilization system and adopting an advanced preparation process, it simultaneously solves the inherent contradictions of particle size control, biological purity, long-term stability and process chemical compatibility.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] This invention provides a composite water-based barrier coating composition. The composition, based on non-volatile solids, has a total weight of 100 wt% and comprises:
[0009] 60 to 90 wt% polyhydroxy fatty acid ester solids;
[0010] 8 to 30 wt% bio-based polyurethane solids;
[0011] 0.3 to 3.0 wt% of bio-based crosslinking agent;
[0012] 0 to 20 wt% of the sum of bio-based plasticizers, bio-based waxes and bio-based additives;
[0013] The polyhydroxyalkanoate solid is provided in the form of an aqueous dispersion with a Z-average particle size of not more than 3 μm; the bio-based polyurethane solid has a bio-based carbon content of not less than 80% and is composed of soft segments and hard segments, wherein the soft segments are selected from one or more of polycaprolactone, polybutylene succinate or polycarbonate diol, and its acid value is not higher than 2 mg KOH / g.
[0014] When the bio-based crosslinking agent is an isocyanate crosslinking agent, the total equivalence ratio of isocyanate groups to hydroxyl and carboxyl groups is between 1.05 and 1.20, for example, it can be 1.05, 1.10, 1.15 or 1.20; when it is a non-isocyanate system, it contains a bio-based epoxy compound and a bio-based polycarboxylic acid or anhydride, and the equivalence ratio of epoxy groups to carboxyl groups is between 0.90 and 1.10, for example, it can be 0.90, 1.00 or 1.10; the overall bio-based carbon content of the non-volatile solids of the composition is not less than 94%.
[0015] Further, the content of solids in the PHA aqueous dispersion can be 60wt%, 65wt%, 67wt%, 70wt%, 75wt%, 80wt%, 85wt%, 89wt%, or 90wt%. The content of solids in the bio-based polyurethane can be 8wt%, 10wt%, 15wt%, 18wt%, 20wt%, 25wt%, or 30wt%. The content of the bio-based crosslinking agent can be 0.3wt%, 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, or 3.0wt%. The total content of the bio-based plasticizer, bio-based wax, and conventional additives can be 0wt%, 1wt%, 4wt%, 5wt%, 8wt%, 10wt%, 15wt%, or 20wt%. The overall bio-based carbon content of the non-volatile solids in the composition can be not less than 94%, for example, 94.4%, 95.2%, 95.8%, 96.5%, 97.4%, or 97.5%.
[0016] In one specific embodiment, the solid content of the PHA aqueous dispersion is 35 to 55 wt%, further comprising 35%, 40%, 45%, 50%, or 55%; and the bio-based polyurethane is composed of soft segments and hard segments, wherein the hard segments of the bio-based polyurethane are composed of reactive residues of an aliphatic diisocyanate and a small molecule chain extender; the aliphatic diisocyanate is selected from one or more of pentylene diisocyanate (PDI), hexamethylene diisocyanate (HDI), or isophorone diisocyanate (IPDI); the chain extender is selected from one or more of 1,3-propanediol, 1,4-butanediol, and isosorbide; the soft segments are selected from one or more of polycaprolactone, polybutylene succinate, or polycarbonate diol, and their acid value is not higher than 2 mg KOH / g. The PHA is one or more of poly(3-hydroxybutyrate) (PHB), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (P34HB), or PHBH.
[0017] In yet another specific embodiment, the composite waterborne barrier coating composition has a viscosity of 500 to 1500 mPa·s at 25°C and a pH value of 6.5 to 7.5.
[0018] Another aspect of the present invention provides a coated paper article. The surface of the article has a coating formed from the aforementioned composition, with a dry coating weight of 6 to 10 g / m². 2 For example, it could be 6g / m 2 7g / m 2 8g / m 2 8.5g / m 2 9g / m 2 or 10g / m2 .
[0019] Combined with appendix Figure 1 The coated paper product of this invention exhibits a specific cross-sectional microstructure. The structure shown in the figure consists of a paper substrate 1 serving as a carrier, and a composite barrier coating 4 coated on the surface of the paper substrate. This composite barrier coating 4 itself is a composite barrier coating composed of two main phases: a PHA barrier phase 2, which serves as the main barrier phase and forms barrier regions within the coating; and a PU toughening and heat-sealing phase 3, which serves as both a toughening and heat-sealing phase, surrounding or filling the polyhydroxyalkanoate phase to form a matrix. This unique two-phase synergistic structure is key to achieving the comprehensive performance of this invention.
[0020] Furthermore, the oxygen translucency (OTR) of the coated paper product is no higher than 12 cm³ under conditions of 23°C and 0% relative humidity. 3 / (m 2 (day), for example, it could be 12cm 3 / (m 2 ·day), 10cm 3 / (m 2 ·day), 9cm 3 / (m 2 ·day), 8cm 3 / (m 2 ·day) or 7cm 3 / (m 2 ·day).
[0021] Furthermore, the water vapor transmission rate (WVTR) of this coated paper product is no higher than 80 g / (m²) under conditions of 38°C and 90% relative humidity. 2 (day), for example, could be 78g / (m 2 ·day), 68g / (m 2 ·day), 65g / (m 2 ·day), 60g / (m 2 ·day), 58g / (m 2 ·day) or 52g / (m 2 ·day).
[0022] Furthermore, the coated paper product, when tested according to ASTM F88 / F88M-23 standards at 140 to 160°C, 0.6 to 0.8 seconds, and 0.3 MPa, has a heat-sealing strength of not less than 9.0 N / 15 mm, for example, not less than 9.2 N / 15 mm, 9.8 N / 15 mm, 10.2 N / 15 mm, 10.8 N / 15 mm, 11.8 N / 15 mm, or 12.8 N / 15 mm.
[0023] In another aspect, the present invention provides a method for preparing the above-described composite waterborne barrier coating composition. The method includes the following steps:
[0024] Step 1. Under stirring, mix the PHA aqueous dispersion, bio-based polyurethane aqueous dispersion and bio-based additives in sequence until homogeneous, and adjust the pH of the system to 6.8 to 7.2;
[0025] Step 2. Pre-emulsify the crosslinking agent separately before use, then add it to the mixture in Step 1, and control the amount according to the aforementioned equivalent ratio, stirring until uniform to obtain the coating composition.
[0026] The present invention also relates to the use of the above-mentioned composite water-based barrier coating composition or coated paper products, specifically for the preparation of oil-resistant, barrier and low-temperature heat-sealing packaging materials for food contact, intended to replace polyethylene film or fluorine-containing coatings.
[0027] Compared with the prior art, the following significant advantages can be obtained by using the present invention:
[0028] Innovative Synergistic Mechanism: This invention creatively designs a biphase synergistic system in which highly crystalline PHA serves as the main barrier phase, providing excellent gas barrier performance; while flexible bio-based PU acts as the toughening and heat-sealing phase, effectively overcoming the fundamental defects of pure PHA coatings, such as high brittleness and narrow heat-sealing window. By precisely controlling the ratio of the two and the formation of the cross-linking network, the complementary advantages of rigid barrier segments and flexible functional segments are achieved at the molecular level, resulting in a synergistic effect of "1+1>2".
[0029] Superior overall performance under thin coating: Based on the above synergistic mechanism, this invention successfully achieves 6 to 10 g / m³ of coating. 2 With extremely low dry coating weight, it simultaneously achieves high barrier properties (OTR≤12, WVTR≤80), excellent low-temperature heat sealability (≥9.0N / 15mm) and outstanding flexibility (barrier retention rate after bending >90%), solving the technical problem that existing technologies cannot achieve these mutually restrictive performance indicators under thin coating.
[0030] A thoroughly green and sustainable solution: This invention goes beyond the main resin, integrating the bio-based concept into the entire solid formulation system, including crosslinking agents and plasticizers. This ensures that the overall bio-based carbon content of non-volatile substances is no less than 94%, achieving an industry-leading level. Combined with its complete biodegradability, excellent repulping performance, and fluorine-free formulation, it provides the market with a truly green packaging solution covering the entire lifecycle from raw material sourcing to waste disposal. Attached Figure Description
[0031] Figure 1 : A schematic diagram of the cross-sectional microstructure of the coating of the present invention on a paper or paperboard substrate.
[0032] In the diagram, 1 is the paper base; 2 is the PHA barrier phase; 3 is the PU toughening and heat-sealing phase; and 4 is the composite barrier coating. Detailed Implementation
[0033] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of this invention should be included within the scope of protection of this invention. Unless otherwise stated, the raw materials used in this invention are commercially available industrial products or can be prepared by conventional methods. Unless otherwise specified, performance testing methods are conducted according to the standards described in the invention summary section.
[0034] Main reagents and raw materials:
[0035] The main reagents and raw materials used in this invention are shown in Table 1 below.
[0036] Table 1. Names, Models, and Suppliers of Major Reagents and Raw Materials:
[0037]
[0038] Main analytical and testing instruments:
[0039] pH meter: Mettler Toledo SevenCompact S210 (accuracy ±0.002 pH, or equivalent).
[0040] Analytical balance: Mettler Toledo ME204E (d=0.1mg, or equivalent).
[0041] Forced air drying oven: Memmert UF110 / UF110plus (room temperature +10~300℃, or equivalent).
[0042] Temperature and humidity chamber / damp shock: ESPEC SH-241 (capable of performing 85°C, 85% RH programs) or equivalent equipment; Binder KMF 115 (10–70°C, 0–95% RH) for other conditioning and aging tests at temperatures below 70°C.
[0043] Viscometer: Brookfield RVT (Spindle #3, 60 rpm, 25°C; periodically verified with standard silicone oil).
[0044] Particle size / potential analyzer: Malvern Zetasizer Nano ZS.
[0045] High-speed disperser / homogenizer: T 25 digital ULTRA-TURRAX, IKA.
[0046] High-pressure homogenizer: AH-100D, ATS Engineering.
[0047] Particle size and Zeta potential analyzer: Zetasizer Nano ZS90, Malvern.
[0048] OTR tester: AMETEK MOCON OX-TRAN 2 / 22.
[0049] WVTR tester: AMETEK MOCON AQUATRAN 3 / 34.
[0050] Tensile testing machine: Instron 5967, used for heat seal strength testing.
[0051] Hot-press sealing instrument: Labthink HST-H3.
[0052] Gelbo Flex Bending Fatigue Tester: Testing Machines Inc. (TMI) Model 173.
[0053] Friction coefficient tester: Labthink MXD-02 or Thwing-Albert FP-2260.
[0054] Blockage tester: Labthink BLD-01 parallel plate blockage tester.
[0055] For cardboard / film thickness measurement: L&W Thickness Tester 51 or Mitutoyo 293 series digital micrometer (with anvil / pressure configured according to ISO 534).
[0056] Scanning electron microscope (SEM): Hitachi SU3500.
[0057] TOC / COD test: Shimadzu TOC-L.
[0058] Gas chromatograph: Agilent 7890B, or an equivalent model such as Agilent 8890.
[0059] Combustion-ion chromatography system: Mitsubishi AQF-2100H coupled with Metrohm 930 Compact ICFlex.
[0060] Laboratory coating machine: RK Print K Control Coater K202.
[0061] Main testing standards:
[0062] Non-volatile matter content: ISO 3251:2019.
[0063] Viscosity: Brookfield RV (Spindle #3, 60 rpm, 25°C).
[0064] Particle size distribution (DLS): ISO 22412:2025; When the Z-mean particle size is ≥1000 nm or close to the upper limit of the instrument range, the volume distribution D is determined by laser diffraction static light scattering ISO 13320:2020. 50 The Z-mean particle size is used as an equivalent criterion. If the relative deviation between DLS and static light scattering results is >20%, the ISO 13322-1 (counting method) microscopic image analysis shall be used as the arbitration. The test report must specify the method, temperature, refractive index of the medium, and distribution type.
[0065] OTR: Dry condition according to ASTM D3985-24 (23°C, 0% RH); wet condition or different humidity conditions according to ASTM F1927-20.
[0066] WVTR: ASTM F1249-20 (38℃, 90% RH).
[0067] Heat seal strength: ASTM F88 / F88M-23 (180° peel, 200 mm / min).
[0068] Heat sealing for sample preparation and windowing: ASTM F2029-16 (2021).
[0069] Flexibility fatigue pretreatment: ASTM F392 / F392M-23 (Gelbo Flex).
[0070] Bio-based carbon content: ASTM D6866-22.
[0071] Biodegradability: ASTM D5338-15 (2021).
[0072] Disintegration rate: ISO 20200:2023.
[0073] Recyclability performance: CEPI Recyclability Laboratory Test Method (Version 3, 2025-02).
[0074] Total organic fluorine (TOF): EN 14582:2016.
[0075] Oil resistance (Kit): TAPPI T 559 cm-12 (R2022).
[0076] Cobb absorbency: TAPPI T441 om-24.
[0077] Blocking tendency: ASTM D3354-21 (parallel plate method, with appropriate fixtures and loads for coated paper samples).
[0078] Static / dynamic coefficient of friction (COF): ASTM D1894-24.
[0079] Sensory migration: DIN 10955:2024.
[0080] Paper basis weight and thickness: ISO 536:2019; ISO 534:2011.
[0081] Chemical equivalence calculations are performed using: acid value (ISO 2114:2000); hydroxyl value (ISO 4629-2:2016); and NCO content (ASTM D2572).
[0082] Regulatory compliance (non-restricted): GB 4806.8-2022; GB 31604.1-2023; EN 1186 (series, current version).
[0083] Quality control (non-limited): VOC content (ISO 11890-2:2020, target ≤50g / L); Zeta potential (ISO13099-2:2012, target −30±10mV for PHA dispersion).
[0084] Examples and Comparative Examples:
[0085] General test conditions: Unless otherwise specified, all OTR / WVTR / heat seal / COF / blocking data are statistically analyzed with n≥5, and the reported mean ± standard deviation is used; OTR sample area ≥50cm², WVTR sample opening diameter 50cm² (or instrument default), clamping and sealing are performed according to the instrument manual. Heat seal sample preparation is performed according to ASTM F2029, heat seal strength is performed according to ASTM F88 / F88M-23, and testing is conducted at 140–160℃, 0.7s, and 0.3MPa; COF is performed according to ASTM D1894-24, blocking according to ASTM D3354-21, and Cobb according to TAPPI T441 om-24. SEM is used to observe the crack morphology after bending. Re-pulping and adhesion are performed according to CEPI V3 (with ISO5263-1 pulping, Somerville sieve and Rapid-Köthen papermaking).
[0086] A general method for preparing composite coatings: In a reactor equipped with a mechanical stirrer, add deionized water according to the formulation amount and start stirring. Slowly add PHA aqueous dispersion, bio-based PU aqueous dispersion, triethyl citrate, carnauba wax emulsion, wetting agent, and defoamer sequentially. Adjust the pH of the system to 7.0 with ammonia. In another container, pre-emulsify the bio-based HDI crosslinking agent or the bio-based epoxide / citric acid crosslinking system, and then slowly pump it into the main reactor. Continue stirring at room temperature for 30 minutes to obtain the final composite waterborne barrier coating.
[0087] Bioten TM General preparation steps for PHA aqueous dispersions:
[0088] The PHA aqueous dispersion used in this embodiment of the invention is prepared using an environmentally friendly solvent-free high-energy homogenization method. The specific steps are as follows:
[0089] Step 1. Dissolve 0.5g PVA in 200mL of deionized water and heat to 80℃ to obtain the aqueous phase.
[0090] Step 2. Melt 10g of PHA powder at 175°C.
[0091] Step 3. In a high-shear homogenizer, slowly add the molten PHA obtained in step 2 to the hot water phase in step 1 at a speed of 10,000 rpm, and continue shearing for 10 minutes to form a crude emulsion.
[0092] Step 4. Immediately transfer the hot crude emulsion to a high-pressure homogenizer preheated to 80°C and homogenize it 5-8 times under a pressure of 80-100 MPa.
[0093] Step 5. After homogenizing, the emulsion is cooled to room temperature while stirring to obtain a milky white, stable aqueous dispersion of PHA. The solid content of each dispersion is 40-45 wt%, and the average particle size D is... 50 The micrometer size should be controlled within the range of 0.5-2.0 μm.
[0094] General method for preparing coated paper products: Select base paper with a basis weight of 80±2 g / m³ 2 A base paper with a thickness of 110±5µm was used as the substrate. Using a laboratory coating machine, the prepared coating was evenly applied to the surface of the base paper by a scraping method. The coated paper was then dried and cured sequentially in ovens at 70, 90, and 110℃, with a dwell time of 2 minutes at each temperature zone. The dry coating amount was determined using the front and back weighing method (ISO 536), after deducting the influence of volatile matter content (ISO 3251); the thickness was verified using a thickness gauge (ISO 534). The dried coated paper was then cured at room temperature for 24 hours before performance testing.
[0095] Examples 1-6 and Comparative Examples 1-4 were prepared according to the general method described above and the formulations (based on the mass of non-volatile solids) given in Table 2 below. The aqueous barrier coatings of Examples 1-6 and Comparative Examples 1-4 were then coated on paper substrates for performance evaluation.
[0096] Table 2. Formulations of Examples and Comparative Examples (Unit: Parts by Mass):
[0097]
[0098] Experimental Results and Analysis:
[0099] The coatings prepared in the examples and comparative examples were coated onto paper substrates, with the dry coating weight controlled at 8.5 ± 0.5 g / m². 2 Test its various performance characteristics.
[0100] Basic performance and sustainability assessment:
[0101] To comprehensively evaluate the basic physical properties, key barrier properties, and sustainability indicators of each coating formulation, and to verify whether they meet the core design objectives of this invention, a series of integrated tests were conducted. These tests aimed to quantify the proportion of bio-based sources in the products, their ability to block oxygen and water vapor, macroscopic coating quality, and ultimate biodegradability.
[0102] Table 3. Basic performance and sustainability test results of the examples and comparative examples:
[0103]
[0104] Analysis: Table 3 shows that all examples meet the requirements of an overall bio-based carbon content of not less than 94% and an OTR of not more than 12 cm⁻¹. 3 / (m 2 •day), WVTR not higher than 80g / (m 2 The technical indicators of the coating (day) show a smooth appearance and high biodegradability, fully achieving the expected goals of this invention. However, the formulations of the comparative examples exceeded the scope of this invention, resulting in significant performance shortcomings: Comparative Example 1 (pure PHA) had an excessively high WVTR and the coating was brittle; Comparative Example 2 (pure PU) had an excessively high OTR; Comparative Example 3 (low PHA content) had an excessively high OTR; and Comparative Example 4 (low PU content) also had a brittle coating.
[0105] Processing and application performance evaluation:
[0106] Heat-sealing performance is crucial for packaging materials to achieve their sealing function and directly relates to their potential for industrial applications. This test aims to evaluate the heat-sealing capability of coatings under specific temperature, time, and pressure conditions, including initial sealing temperature, optimal heat-sealing range, and final peel strength, to verify their effectiveness as a packaging sealing layer.
[0107] Table 4. Heat sealing performance test results of the examples and comparative examples (time: 0.7s, pressure: 0.3MPa):
[0108]
[0109] Note: Failure modes: A - Adhesion failure, C - Cohesion failure, S - Substrate tearing.
[0110] Analysis: Table 4 shows that all embodiments have a wide and suitable low-temperature heat-sealing window, high heat-sealing strength, and ideal substrate tearing (S) failure mode, indicating that the coating's cohesive strength and adhesion to the substrate are superior to its own strength. Comparative Example 1, however, has almost no heat-sealing properties; Comparative Example 4 has insufficient heat-sealing strength and an undesirable failure mode, demonstrating the crucial role of the PU component in the formulation of this invention for achieving reliable heat sealing.
[0111] Oil resistance is a core requirement for food packaging materials, especially those used in applications involving contact with oily foods. This section evaluates the coating's ability to resist penetration by oily agents with varying surface tensions using standard Kit-level testing to quantify its oil resistance rating.
[0112] Table 5. Oil resistance (Kit) test results for the examples and comparative examples:
[0113]
[0114] Analysis: Table 5 shows that the Kit grade in all embodiments is no lower than level 8, achieving a high oil resistance standard and effectively replacing fluorinated coatings. However, excessively high PU content (Comparative Examples 2 and 3) leads to a significant decrease in oil resistance, highlighting the necessity of a high PHA content in the formulation of this invention to achieve oil resistance.
[0115] To achieve the recycling of packaging materials, their recyclability in standard papermaking processes is crucial. This section evaluates the repulping performance of coated paper products based on the authoritative industry standard CEPI V3, focusing on indicators such as waste rate, adhesive contamination, and fiber recovery rate to determine their friendliness to recycling systems.
[0116] Table 6. Repulping performance test results of the examples and comparative examples (CEPI V3):
[0117]
[0118] Analysis: Table 6 demonstrates that all embodiments exhibit excellent repulping performance, with all indicators showing good results, high fiber recovery rate, and high paper appearance grade, meeting the requirements of a circular economy. In contrast, unreasonable formulations (especially excessively high PU content) lead to a significant increase in waste residue, DCS index, and adhesive area, severely impacting recycling quality and thus proving the superiority of the formulation of this invention.
[0119] Given the stringent global regulations on perfluorinated and polyfluoroalkyl substances (PFAS), proving that a product is fluorine-free is a prerequisite for market entry. This test uses combustion-ion chromatography to accurately measure the total organic fluorine (TOF) content to confirm that no fluorinated chemicals have been intentionally added to the product of this invention.
[0120] Table 7. Results of total organic fluorine (TOF) content tests in the examples and comparative examples:
[0121]
[0122] Analysis: The results in Table 7 consistently show that none of the formulations in the embodiments and comparative examples of this invention contain any artificially added fluorine-containing substances, which complies with environmental regulations.
[0123] Flexible packaging undergoes repeated bending and folding during distribution and use, which can cause the barrier coating to crack and fail. This experiment uses the Gelbo Flex bending tester to simulate this physical stress and evaluates the flexibility and durability of the coating by measuring the changes in barrier performance before and after bending.
[0124] Table 8 Barrier retention rate after bending fatigue in the examples and comparative examples (Gelbo Flex, Level D, 100 cycles):
[0125]
[0126] Analysis: Table 8 shows that the coatings in the examples all maintained very high barrier properties after being bent, demonstrating excellent flexibility and durability, and were able to adapt to the physical challenges of actual circulation. In contrast, pure PHA (Comparative Example 1) almost completely lost its barrier properties due to its brittleness, and the retention rates of other comparative examples were also significantly lower than those in the examples, further demonstrating the key role of PU in improving flexibility in the formulation.
[0127] In roll-to-roll industrial production and storage, adhesion (i.e., blockage) between coatings is a serious problem that can lead to material spoilage. This test evaluates the anti-blockage ability of coatings by pressing them face-to-face for a period of time under set temperature and pressure, which is an important indicator of their processing stability.
[0128] Table 9. Results of the blocking tendency test for the examples and comparison examples (50℃, 24h, 1.0kg):
[0129]
[0130] Analysis: Table 9 demonstrates that all embodiments of the present invention exhibit no tendency to blockage, making them suitable for roll-to-roll processing and storage. However, high PU content (Comparative Examples 2 and 3) can lead to severe adhesion problems, which is a technical defect that the present invention needs to avoid.
[0131] The coefficient of friction (COF) of the coated surface is a key parameter affecting its smooth operation on high-speed automated packaging lines. Both excessively high and low COFs can lead to processing problems. This experiment aims to determine the static and dynamic COFs of the coated surface to evaluate its operability in actual production.
[0132] Table 10. Friction coefficient test results of the examples and comparative examples (coating-coating):
[0133]
[0134] Analysis: The examples in Table 10 have a moderate coefficient of friction, which is beneficial for the smooth operation of automated packaging lines. However, the coefficients of friction in Comparative Examples 2 and 3 are too high, which can easily lead to sticking; while Comparative Examples 1 and 4 may be too slippery, which is not conducive to stacking.
[0135] Packaging materials may come into contact with moisture during storage or use, therefore water resistance is a fundamental requirement. This experiment uses the standard Cobb test method to evaluate the ability of a coating per unit area to resist liquid water penetration by measuring the amount of water absorbed within a specified time.
[0136] Table 11. Results of water absorption tests (Cobb) for the examples and comparative examples:
[0137]
[0138] Analysis: Table 11 shows that all examples exhibit good water resistance, with Cobb 60 values all below 20 g / m³. 2 The comparative examples 2 and 3, which have high PU content, exhibited poor water resistance, further supporting the rationality of the formulation in this invention.
[0139] As a food contact material, the coating itself must not impart any off-flavors or odors to the food. This experiment used a professional sensory evaluation team to assess the samples according to DIN standards to ensure their sensory inertness when in contact with food, which is a crucial step in ensuring food safety and consumer acceptance.
[0140] Table 12 Sensory transfer test results of the examples and comparative examples (DIN 10955:2024):
[0141]
[0142] Analysis: All examples passed the sensory migration assessment with an odor score of 0, indicating that they are safe for food contact. The comparative examples also passed the sensory migration assessment, suggesting that this indicator is mainly related to the purity of the raw materials. High PU content may introduce a slight odor, but it is still within the acceptable range.
[0143] Industrial applicability verification experiments:
[0144] 1. Resistant to oil penetration in hot oil contamination scenarios.
[0145] To simulate the harsh scenarios of hot oil contact in real-world applications such as food delivery and baking, this experiment brought edible oil mixed with red dye into contact with the coating at high temperatures. The oil penetration was visually observed to more intuitively evaluate the coating's heat resistance to oil.
[0146] Table 13. Results of hot oil grease penetration tests for the examples and comparative examples (70℃, 30min):
[0147]
[0148] Analysis: Table 13 shows that all embodiments of the present invention maintain excellent permeability resistance in high-temperature oily environments, meeting stringent food packaging requirements. However, excessively high PU content (Comparative Examples 2 and 3) leads to a significant decrease in heat-resistant oil performance.
[0149] 2. WVTR stability in humid / heating / condensing environments.
[0150] Packaging materials may experience a decline in barrier properties due to condensation or moisture absorption when subjected to drastic temperature changes (such as removal from refrigeration) or high humidity environments. This experiment simulates high temperature and high humidity shock conditions to test the change in the coating's WVTR, thereby verifying its performance stability under harsh environments.
[0151] Table 14. WVTR test results after hydrothermal treatment in the examples and comparative examples:
[0152]
[0153] Analysis: Table 14 shows that the coatings in the embodiments of the present invention can still maintain extremely high water vapor barrier performance under humid heat shock. In contrast, pure PHA (Comparative Example 1) will crack due to thermal shock, while coatings with high PU content (Comparative Examples 2 and 3) will swell due to water absorption, resulting in a serious decrease in barrier performance.
[0154] 3. Heat-sealed and resistant to contamination.
[0155] In actual packaging lines, the sealing area is sometimes inevitably contaminated by contents (such as oil droplets or water droplets). This experiment aims to evaluate the heat-sealing capability of the coating in the presence of oil or water contamination at the sealing interface, which is an important indicator of its process robustness and reliability in practical applications.
[0156] Table 15. Test results of heat-sealing contamination resistance of the examples and comparative examples:
[0157]
[0158] Analysis: The data in Table 15 show that even in the presence of oil and water contamination, the coating of the embodiments of the present invention can still achieve high-strength heat sealing and exhibits an ideal failure mode, demonstrating excellent process adaptability. In contrast, Comparative Examples 1, 2, 3, and 4 failed to form a reliable seal under contaminated conditions.
[0159] 4. Food contact migration (regulatory adaptation, example).
[0160] Total migration is one of the ultimate and most critical indicators for assessing the safety of food contact materials, directly impacting consumer health. This test, based on Chinese national food safety standards, uses food simulants of different properties under stringent conditions to measure the total amount of non-volatile substances migrating from the coating into the simulants, verifying whether it meets regulatory limits.
[0161] Table 16 Overall migration test results of the examples and comparative examples (GB 4806.8-2022):
[0162]
[0163] Analysis: Table 16 presents the overall migration test results for the Chinese market. Experimental data show that, under conditions simulating different types of food, the overall migration levels of all tested samples were far below the 10 mg / dm² limit specified in the national standard GB 4806.8-2022. All embodiments of this invention exhibited extremely low migration levels, demonstrating its high safety as a food contact material.
[0164] 5. Observe the coating's resistance to flexural cracking.
[0165] This experiment used scanning electron microscopy (SEM) to directly observe the surface morphology of the coating after undergoing bending fatigue testing at the microscale. This aims to verify the results of the barrier retention rate test (Table 8) from a mechanistic perspective, and to intuitively reveal the fundamental differences in flexibility between different formulations by quantifying the density of microcracks.
[0166] Table 17 Microscopic morphology of coatings after bending in the examples and comparative examples (100 cycles / Level D):
[0167]
[0168] Analysis: The microscopic observation results in Table 17 directly demonstrate the excellent flexibility of the formulation of this invention. The coatings in the examples showed almost no cracks or only a very small number of microcracks after repeated bending, which is highly consistent with their high barrier retention rate (Table 8). In contrast, the pure PHA coating (Comparative Example 1) exhibited severe brittleness, while the coating with insufficient PU content (Comparative Example 4) also showed significant cracking.
[0169] 6. Coating disintegration performance (ISO 20200).
[0170] Biodegradability (Table 3) focuses on the chemical transformation of materials under the action of microorganisms, while disintegration focuses on their physical disintegration ability in a composting environment. Disintegration testing according to ISO 20200 standards is a key step in proving that a material is "compostable." This experiment aims to verify whether the coating can be fully broken down within a specified time to meet the requirements of industrial composting.
[0171] Table 18. Disassembly performance test results of the examples and comparative examples (ISO 20200:2023, 12 weeks):
[0172]
[0173] Analysis: Table 18 shows that after 12 weeks of industrial composting, the residual mass of the coated paper products in all embodiments of the present invention was less than 10%, and there were no visible fragments, meeting the disintegration requirements of the ISO 20200 standard. This is corroborated by the ASTM D5338 biodegradability data (Table 3). Comparative Examples 2 and 3, with excessively high PU content, could not completely disintegrate, demonstrating the superiority of the present invention's formulation in ensuring complete biodegradability.
[0174] 7. Verification of quality control items.
[0175] To ensure quality stability and batch consistency from raw materials to final products, it is necessary to establish key quality control (QC) items. This section tests the volatile organic compound (VOC) content of the coating and the zeta potential of the system. The former relates to compliance with environmental and safety regulations, while the latter directly reflects the storage stability of the water-based dispersion system.
[0176] Table 19 Test results of quality control items for the examples and comparative examples (ISO 11890-2:2020):
[0177]
[0178] Analysis: The test results in Table 19 show that the VOC content of the representative coating products all meet the low volatility requirements. The Zeta potential of the key raw material PHA aqueous dispersion is within the ideal stability range. In the finished coatings, the absolute values of the Zeta potential in all examples are relatively high (greater than 35mV), indicating that the system has excellent storage stability. In contrast, the absolute values of the Zeta potential in Comparative Examples 2 and 3 are relatively low, which may pose a risk of flocculation during long-term storage, thus ensuring the quality of the system of this invention.
[0179] Comprehensive Result Analysis:
[0180] Analysis of the impact of key components on performance:
[0181] The ratio of PHA aqueous dispersion solids (PHA) to bio-based polyurethane solids (PU): The core of this invention lies in achieving a balance of comprehensive performance by precisely controlling the ratio of the hard and brittle barrier phase PHA to the flexible toughening phase PU. The design of the embodiments verifies the range defined by this invention: PHA 60 to 90 wt%, PU 8 to 30 wt%.
[0182] When the PHA content is at the high end of the range, such as in Example 2 (PHA 90%) and Example 5 (PHA 89%), the coating exhibits the best oxygen barrier (OTR 7 to 8) and oil resistance (Kit grade 10), but slightly poorer flexibility (barrier retention after bending is about 90%, and the coating appearance is slightly brittle).
[0183] When the PHA content is at the lower end of the range, such as in Example 3 (PHA is 60%), the coating exhibits the best flexibility (barrier retention rate of 98% after bending), the widest heat seal window and the highest heat seal strength (12.8 N / 15 mm), but the gas barrier performance is at the critical value of the index (OTR is 12).
[0184] Example 1 (PHA 75%) and Example 4 (PHA 67%) demonstrate the ideal balance of various performance characteristics.
[0185] Comparative Examples 1 to 4 clearly demonstrate the consequences of exceeding this range: pure PHA (Comparative Example 1) lacks heat-sealing properties and flexibility; excessively high PU content (Comparative Examples 2 and 3) severely sacrifices barrier properties, oil resistance, and resizing properties; and excessively low PU content (Comparative Example 4) fails to effectively toughen the material, resulting in insufficient heat-sealing strength.
[0186] Bio-based crosslinking agent: The crosslinking agent content is limited to 0.3 to 3.0 wt% in this invention. Examples 1 to 5 use a bio-based HDI crosslinking agent with a dosage between 0.5 and 2.0 wt%, while Example 6 uses a bio-based epoxy / carboxylic acid system for crosslinking with a total dosage of 2.0 wt%. Data comparison (e.g., Example 1 vs. Example 6) shows that different crosslinking paths and dosages within this range can all result in coatings with excellent overall performance, demonstrating the universality of the technical solution of this invention. The formation of the crosslinking network is crucial to the cohesive strength, durability (flexural fatigue), and adhesion of the coating.
[0187] Bio-based plasticizers and waxes, etc.: The total amount of additives in this invention is limited to 0 to 20 wt%. A comparison of Example 2 (without plasticizer) and Example 5 (with 1% plasticizer) shows that the addition of plasticizer can effectively improve the flexibility of high PHA content formulations and eliminate the "slightly brittle" appearance. The addition of wax can control surface energy and surface morphology, which generally helps reduce the risk of clogging and obtain a suitable COF; the directional effect on COF is related to the dosage, wax type, and substrate roughness, and should be determined by actual measurements (see Table 10).
[0188] Sustainability and compliance analysis:
[0189] All embodiments achieved an overall bio-based carbon content of no less than 94% and exhibited excellent biodegradability. Repulping performance tests showed that the formulations of this invention generated significantly less waste and adhesives than the comparative examples, with high fiber recovery and environmental friendliness. Furthermore, all samples passed total organic fluorine tests and sensory migration tests, demonstrating their safety for food contact applications.
[0190] Comprehensive evaluation of processing and application performance:
[0191] By introducing evaluations that closely resemble practical applications, such as bending fatigue, blockage, coefficient of friction, and water absorption, the industrial applicability of the invention was further verified. The sample examples maintained high barrier properties even after physical deformation, were not prone to sticking during storage and transportation, possessed a smooth surface suitable for automated packaging lines, and effectively resisted moisture penetration, fully demonstrating their reliability as packaging materials.
[0192] In summary, by precisely controlling the ratio of PHA and PU with high bio-based content, and combining them with bio-based crosslinking agents and additives, this invention has successfully prepared a composite waterborne barrier coating that combines high barrier properties, excellent heat-sealing properties, complete biodegradability, high bio-based content, and superior processing and application performance, thus overcoming many shortcomings of existing technologies.
[0193] Those skilled in the art should understand that the above embodiments are merely exemplary and are not intended to limit the scope of the present invention. Any modifications, equivalent substitutions, improvements, etc., made to the technical solutions of the present invention within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A composite water-based barrier coating composition, characterized in that, The total amount of non-volatile solids is 100 wt%, comprising: 60 to 90 wt% polyhydroxy fatty acid ester solids; 8 to 30 wt% bio-based polyurethane solids; 0.3 to 3.0 wt% of bio-based crosslinking agent; 0 to 20 wt% of bio-based plasticizers, bio-based waxes and conventional additives; The polyhydroxyalkanoate solid is provided as an aqueous dispersion with a Z-average particle size of not more than 3 μm; the bio-based polyurethane solid has a bio-based carbon content of not less than 80% and is composed of soft segments and hard segments, wherein the soft segments are selected from one or more of polycaprolactone, polybutylene succinate, or polycarbonate diol, and their acid value is not higher than 2 mg KOH / g; when the bio-based crosslinking agent is an isocyanate crosslinking agent, the total equivalence ratio of isocyanate groups to hydroxyl and carboxyl groups is between 1.05 and 1.20; when it is a non-isocyanate system, it contains bio-based epoxy compounds and bio-based polycarboxylic acids or anhydrides, and the equivalence ratio of epoxy groups to carboxyl groups is between 0.90 and 1.10; the overall bio-based carbon content of the non-volatile solid of this composition is not less than 94%.
2. The composite water-based barrier coating composition according to claim 1, characterized in that, The polyhydroxy fatty acid ester is one or more of poly(3-hydroxybutyrate), poly(3-hydroxybutyrate-co-3-hydroxyvalerate), poly(3-hydroxybutyrate-co-4-hydroxybutyrate), or poly(3-hydroxybutyrate-co-3-hydroxyhexanoate).
3. The composite water-based barrier coating composition according to claim 1, characterized in that, The solid content of the polyhydroxy fatty acid ester aqueous dispersion is 35 to 55 wt%.
4. The composite water-based barrier coating composition according to claim 1, characterized in that, The composition has a viscosity of 500 to 1500 mPa·s at 25°C and a pH of 6.5 to 7.
5.
5. A coated paper product, characterized in that, The coated paper product surface has a coating formed by the composition according to any one of claims 1 to 4, with a dry coating weight of 6 to 10 g / m². 2 .
6. The coated paper product according to claim 5, characterized in that, The oxygen permeability of the coated paper product is no higher than 12 cm under conditions of 23°C and 0% relative humidity. 3 / (m 2 ·day).
7. The coated paper product according to claim 5, characterized in that, The water vapor transmission rate of the coated paper product is no higher than 80 g / (m³) under conditions of 38°C and 90% relative humidity. 2 ·day).
8. The coated paper product according to claim 5, characterized in that, The coated paper product, when tested according to ASTM F88 / F88M-23 standards at 140 to 160°C, 0.6 to 0.8 seconds, and 0.3 MPa, has a heat-sealing strength of not less than 9.0 N / 15 mm.
9. A method for preparing a composite waterborne barrier coating composition according to any one of claims 1 to 4, characterized in that, Includes the following steps: Step 1. Under stirring, the polyhydroxyalkanoate aqueous dispersion, the bio-based polyurethane aqueous dispersion and the bio-based additive are mixed evenly in sequence, and the pH value of the system is adjusted to 6.8 to 7.2; Step 2. Pre-emulsify the crosslinking agent separately before use, then add it to the mixture in Step 1, and control the amount according to the equivalent ratio in claim 1, and stir until uniform to obtain the coating composition.
10. Use of the composite waterborne barrier coating composition according to any one of claims 1 to 4 or the coated paper article according to any one of claims 5 to 8 in the preparation of oil-resistant, barrier, and low-temperature heat-sealing packaging materials for food contact, said use being intended to replace polyethylene lamination or fluorinated coating.
Citation Information
Patent Citations
Dispersions of polyhydroxyalkanoates in water
CA2239980C
Coated paper
CN115698427A
PHA composition and preparation method therefor
EP4239028A1
Biodegradable paper barrier laminate
US20220033158A1
Biodegradable coatings based on aqueous PHA dispersions
WO2020036843A1
Cited By
Biomass-sourced PHA oil-resistant and moisture-permeable coating, coated paper and preparation method
CN121272776A
Method and system for integrating high-flux steam exhaust, hot-pressing densification and controlled crystallization of water-based PHA (Polyhydroxyalkanoate) coating wet film
CN121428864A
Integrated method and system for high-throughput steam venting, hot-pressing densification, and controlled crystallization of aqueous pha coating wet films
CN121428864B